2022
DOI: 10.1057/s41276-022-00390-3
|View full text |Cite
|
Sign up to set email alerts
|

Cascading disasters: The impact of hurricane Maria and Covid-19 on post-disaster Puerto Rican migrants’ adaptation and integration in Florida

Abstract: Based on data from 103 surveys of Puerto Rican migrants living in Florida and 54 in-depth interviews with a subgroup of them, we examine how Puerto Ricans who left the archipelago after Hurricane Maria have navigated settlement in their new homes. In this article, we observed and classified our participants’ descriptions of how they managed opportunities and challenges regarding education, employment, and social relations, the traditional benchmarks for the assessment of societal integration. We also observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…In the context of societal and economic impacts, damages after the hurricane and the slow recovery led to mass migration from the affected areas. In the aftermath of the earthquake series, the number of individuals leaving Puerto Rico increased (Sanchez, 2020;Aranda et al, 2022). This included a large number of small business owners supporting the tourism industry.…”
Section: Reconnaissance Methodsmentioning
confidence: 99%
“…In the context of societal and economic impacts, damages after the hurricane and the slow recovery led to mass migration from the affected areas. In the aftermath of the earthquake series, the number of individuals leaving Puerto Rico increased (Sanchez, 2020;Aranda et al, 2022). This included a large number of small business owners supporting the tourism industry.…”
Section: Reconnaissance Methodsmentioning
confidence: 99%
“…In a recent study, Aranda et al (2023) found that challenges related to adaptation after migration, such as rebuilding social networks, facilitating children's education, and finding and keeping well-remunerated work were made more difficult for Puerto Rican climate migrants during the COVID-19 pandemic. Referring to these events, including the impact of the hurricane, as cascading disasters (Pescaroli & Alexander, 2015), they argued that the cumulative impact of these disasters and transitions deeply affected (and during the lockdown phase of the pandemic, halted) the social integration process.…”
Section: A Word On Subjective Well-being and Mental Healthmentioning
confidence: 99%
“…While these measures resulted in arresting the spread of the epidemic, they also seriously impacted the operation of the economy, society, and people's normal life (15). Against the background of the increasing normalization of epidemic prevention and control, it has become imperative for different regions to adopt scientific and accurate epidemic control measures customized to local conditions and times so as to balance the dual purposes of epidemic prevention and keeping the economy and society functional (16)(17)(18)(19). Therefore, a key challenge to dealing with the outbreak has been the data and methods that should be used to study and assess the scale of the epidemic and how to understand the laws of epidemic transmission, and then choose the scientific and accurate epidemic control measures (20-23).…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, with the development of big data and cloud computing technology, new methods of analyzing and predicting epidemics have emerged. Wada, Milinovich, Gluskin, and others used the Google Index to predict infectious diseases, such as influenza, dengue fever, and Ebola (16)(17)(18)(19)34). Liu and Chen used the Baidu index to predict the H7N9 epidemic (35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%